A festa em Pindaré-Mirim: nos trilhos da história a afirmação de uma identidade - Costa, Maria Zenaide (2008)
This dissertation is the antrophology study about a Party in Pindaré-Mirin, in Maranhão. This city has the uncommon aspect to its big blend. The popular and religious partes-cadence, regularity, the big number of this, the style confirm of the festivity soul and the spirit of the population. The datuon of the research were obtained through of the country in the 2004, 2005, 2006 and 2007 years. The analyse went the party identity teoric way that we concentrated ours bases to understand the daily party. We observe the social phenomenon of the transformation of the persons and its participation